Moodle gradebook : explore the Moodle gradebook and discover how to set up and customize it to track students' progress - Barrington, Rebecca (Community experience distilled., 2014)
This book is for teachers and administrators who have experience with Moodle. Basic knowledge of Moodle 2.x will be required, but no prior knowledge of grade functions is needed. This book will help you utilize the full functionality of Version 2.7.